If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 6 + 2x = 12 + 4x Reorder the terms: 6 + 8x + 2x = 12 + 4x Combine like terms: 8x + 2x = 10x 6 + 10x = 12 + 4x Solving 6 + 10x = 12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + 10x + -4x = 12 + 4x + -4x Combine like terms: 10x + -4x = 6x 6 + 6x = 12 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + 6x = 12 + 0 6 + 6x = 12 Add '-6' to each side of the equation. 6 + -6 + 6x = 12 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 12 + -6 6x = 12 + -6 Combine like terms: 12 + -6 = 6 6x = 6 Divide each side by '6'. x = 1 Simplifying x = 1
| 4x-8=8x+7-7x | | 5(-17c+53)=-7(5c-45) | | 120=x | | 121=-8m+7(1-7m) | | -10-1=7x-5-x | | -18.04-4.9v+1.6v=14.7v+4(-18.1v+19.97) | | X(a+3)+y(a+3)=0 | | -3(8-11j)=-5(12-6j) | | -3=3x-6x+18 | | 4y-8x=10 | | 55x-11y=253 | | -3(8-11j)=-5(12-j) | | -5d+19-4d=-6(4d+19)-4d | | 8x-15-4x=13 | | 15x+(15)=6 | | 5(-6n+3)=165 | | -4(-18+6n)=-6(13n+15) | | 3x-7=14+2 | | 4x-4-x=-4 | | 11-3s=8 | | 1(-7x+1)=-55 | | 5(-6+3)=165 | | y=3sinx+-4 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16 | | 7x-3-6x=3 | | (3y-28)/7=y/3 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16t | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.6t | | 7x+(10)=3 | | (x-28)/7=y/3 | | -5(5x+3)=45 | | 30(c+4)=900 |